Biosynthesis of silver nanoparticles using brown marine macroalga, Sargassum muticum aqueous extract - Azizi, Susan; Namvar, Farideh; Mahdavi, Mahnaz; Ahmad @ Ayob, Mansor; Mohamad, Rosfarizan (MDPI, 2013)
Biological synthesis of nanoparticles is a relatively new emerging field of nanotechnology which has economic and eco-friendly benefits over chemical and physical processes of synthesis. In the present work, for the first time, the brown marine algae Sargassum muticum (S. muticum) aqueous extract was used as a reducing agent for the synthesis of nanostructure silver particles (Ag-NPs). Structural, morphological and optical properties of the synthesized nanoparticles have been characterized systematically by using FTIR, XRD, TEM and UV–Vis spectroscopy. The formation of Ag-NPs was confirmed through the presence of an intense absorption peak at 420 nm using a UV–visible spectrophotometer. A TEM image showed that the particles are spherical in shape with size ranging from 5 to 15 nm. The nanoparticles were crystalline in nature. This was confirmed by the XRD pattern. From the FTIR results, it can be seen that the reduction has mostly been carried out by sulphated polysaccharides present in S. muticum.